DFT study of the effect of the electrode potential on anchoring of metal-molecule hybrids - Aranda Ruiz, Daniel; Soto-Martín, Juan; Otero-Fernández-de-Molina, Juan Carlos; Ávila-Ferrer, Francisco José (My University, 2018)
The impact of the molecular adsorption process on the electronic structure is the key in phenomena involved in electrochemistry, catalysis, molecular electronics, SERS, photoelectric conversion, etc. The effect of the electrode potential on a collection of relevant systems, commonly used as SERS adsorbates, has been investigated. These molecules have been classified in groups (Gi) based on their charge transfer (CT) excited state behaviour vs the electrode as follows: pyridine and pyrazine (G1), adenine and protonated adenine (G2), benzoate and isonicotinate (G3) and finally chloride and cyanide (G4). The effect of electrode potential were modelled with Molecule-Agnq charged hybrid systems, were q=0,1 and n=2, 3, 5 and 7, through the charge per metallic atom qeff=q/n. As a conclusion, we have found differentiated correlations for the charge injection on the metal, the molecule-metal affinity and the excited CT states energies.
Keywords: Qúimica física; DFT calculations; Metal-molecule hybrids